OPTIMISASI MANAJEMEN ASET TETAP DAERAH DALAM MEWUJUDKAN GOOD GOVERNANCE DI PEMERINTAH PROVINSI DKI JAKARTA - Aprilia, Ika; Syaukat, Yusman; Falatehan, A. Faroby (Jurnal Manajemen Pembangunan Daerah, 2018)
ABSTRACTLocal autonomy means that local governments are given freedom of action to manage and develop their own regions according to theireach condition, characters and potency. The core of local autonomy is democratization and empowerment. It is expected that the emerging democratization brings good governance into reality including good governance, both on the management of local finance and local assets. Assets or the active is one of components in the Local Government Financial Report, in which the greatest sub component is fixed assets. Therefore, good governance on fixed assets will support the efforts that have been made by the Province of DKI Jakarta to realize the good governance. Management of assets or items own by local authorities, according to Permendagri Nomor 19 tahun 2016, consists of several stages that can be classified into four managerial functions, which are planning, organizing, mobilizing or executing and controlling and monitoring. This study utilized primary and secondary data using an analysis method of gap analysis and qualitative description. Results of the study indicated that there was still a “partial gap” for each managerial function in asset management. All managerial functions had been executed moderately well in the asset management; however, the functions should be optimized further to be consistent with the prevailing laws. Based on the gap analysis, the causes of the weaknesses of asset management and the strategy move to overcome the weaknesses in the management of the most needed assets currently in the Province of DKI Jakarta.Key Words: Managerial Function, Gap Analysis and Optimizing Asset Management StrategyABSTRAKOtonomi daerah bermakna bahwa pemerintah daerah diberikan keleluasaan untuk mengelola dan mengembangkan daerahnya sesuai kondisi, karakter dan potensinya masing-masing. Inti dari otonomi daerah adalah demokratisasi dan pemberdayaan. Demokratisasi yang ingin dimunculkan adalah mewujudkan good governance, termasuk di dalamnya tata kelola yang baik atas pengelolaan keuangan daerah dan aset daerah. Aset atau aktiva merupakan salah satu komponen dalam Laporan Keuangan Pemerintah Daerah, dengan sub komponen terbesarnya adalah aset tetap. Oleh karena itu, dengan pengelolaan aset tetap yang baik, akan mendukung upaya pemerintah Provinsi DKI Jakarta mewujudkan good governance. Pengelolaan aset atau barang milik daerah menurut Peraturan Menteri Dalam Negeri Nomor 19 Tahun 2016 terdiri dari beberapa tahapan, yang dapat diklasifikasikan secara fungsi manajerial ke dalam 4 fungsi yaitu perencanaan, pengorganisasian, penggerakan atau pelaksanaan serta pengendalian dan pengawasan.  Penelitian ini menggunakan data primer dan sekunder, dengan metode analisis adalah gap analisis dan deskripsi kualitatif. Hasil penelitian menunjukkan hasil masih ada “partial gap” untuk setiap fungsi manajerial pengelolaan aset. Semua fungsi manajerial telah dijalankan dengan cukup baik dalam pengelolaan aset, namun masih perlu dioptimalkan lebih lanjut agar sesuai dengan ketentuan yang berlaku. Berdasarkan analisis gap diperoleh penyebab kelemahan pengelolaan aset sekaligus langkah strategi untuk mengatasi kelemahan dalam pengelolaan aset yang paling dibutuhkan saat ini di Pemprov DKI Jakarta.Kata Kunci: Fungsi Manajerial, Gap Analisis, Dan Strategi Optimalisasi Manajemen Asset